Multidiscplinary team members’ challenges related to disabled adolescents’ social and domestic processes of adaptation - Ghazaryan, Tatev
This study aims to identify and analyze the main difficulties and obstacles faced by multidisciplinary team members - specialists working in the field of rehabilitation while working with disabled adolescents. A special questionnaire for data collection including open and closed-ended questions was developed. In face and online surveys were conducted with the members of the multidisciplinary team working with disabled adolescents in different rehabilitation centers and specialized institutions in 7 different regions of Armenia. Detection, study, and evaluation of issues related to difficulties while performing daily activities by disabled adolescents due to the lack of appropriate tools do not allow specialists to carry out a systematic evaluation and monitor the process and progress. The other problem identified is related to the fact that most of the intervention organized in different centers is not continuous and systematic, as it is limited by unfavorable environmental conditions, lack of assistive devices and special equipment, as well as by the awareness and lack of knowledge of the specialists working in the field.
Keywords: Disabled adolescents